Research on the Traffic Flow Control of Urban Occasional Congestion Based on Catastrophe Theory - Yang Xu; Duo Jia Zhang; Xin Zhang; Kin Keung Lai; Bing Su (Journal of Advanced Transportation)
Aimed at the problem of occasional congestion control, the cusp catastrophe theory is used to establish the catastrophe model of the urban road system under occasional congestion, finding breakpoints and analyzing stability after urban road system catastrophes by constructing the energetic function; based on the catastrophe characteristics of the urban road system, the feasibility method of congestion control is discussed. The results show that the control method of traffic flow based on catastrophe characteristics of the urban road system can effectively improve the efficiency of the road system in theory. Finally, the applicability of the control method based on catastrophe characteristics is analyzed by examples under different occasional congestion situations.